Colonel William A. Blair house at 210 S. Cherry Street, 1924. - Unknown (Forsyth County Public Library, 1924)
Source: Booklet, "Art Work of Piedmont Section of North Carolina, " 1924.
Colonel William A. Blair house at 210 S. Cherry Street, 1924.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources